Secondary Level Teachers’ Professional Development through Research and Development Project - Sharma, Laxmi (Bodhi: An Interdisciplinary Journal, 2023)
This study explores the lived experiences of Nepali public secondary level school teachers in taking initiatives for their professional development, and the support they received in research and development projects. The data were collected through conducting in-depth interviews with five teachers teaching in public schools run under the education trust of Pokhara and Kathmandu in Nepal. Findings revealed that the Research and Development Project introduced in these selected schools turned out to be supportive of teachers ‘professional development in several ways. Their involvement in the Research and Development Project offered them opportunities to form a new identity and developed skills in self-reflection. This opportunity has contributed to creating a positive impact on improving classroom practices and enhancing teachers’ professional development. Future research might explore modes of effective interventions for helping teachers to grow in their professional practices.